Evaluation on Antidiabetic Properties of Medicinal Plants from Myanmar - Dongdong Zhang; Karuppusamy Arunachalam; Yuehu Wang; Yu Zhang; Jun Yang; Pyae Phyo Hein; Aye Mya Mon; Jianwen Li; Angkhana Inta; Xuefei Yang (The Scientific World Journal)
Objectives. To explore the effective and safe medicines for treating diabetes. Methods. Hydroalcoholic extracts of 130 medicinal plants belonging to 66 families were evaluated using porcine pancreatic lipase (PPL) inhibition and glucose uptake methods together with a literature review. Results. The extracts of 22 species showed the PPL inhibition activity; 18 extracts of 15 species stimulated glucose uptake in 3T3-L1 adipocytes. Among them, Mansonia gagei J.R. Drumm., Mesua ferrea L., and Centella asiatica (L.) Urb. exhibited both activities. The extracts of Caladium lindenii (André) Madison rhizomes and Azadirachta indica A. Juss. leaves presented the utmost lipase inhibitory activity with IC50 of 6.86 ± 0.25 and 11.46 ± 0.06 μg/mL, respectively. The extracts of Coptis teeta Wall. rhizomes and Croton tiglium L. seeds stimulated the maximum glucose uptake. Ten species are reported to have antidiabetic activity for the first time. Flavonoids and triterpenoids are the dominant antidiabetic compounds in selected medicinal plants from Myanmar. Conclusions. P. zeylanica, L. cubeba, H. crenulate, M. gagei, C. teeta, and M. ferrea are worthy to advance further study according to their strong antidiabetic activities and limited research on effects in in vivo animal studies, unclear chemical constitutes, and safety.